High‐Resolution Nighttime Temperature and Rock Abundance Mapping of the Moon Using the Diviner Lunar Radiometer Experiment With a Model for Topographic Removal. Issue 2 (4th February 2023) - Powell, T. M.; Horvath, T.; Robles, V. Lopez; Williams, J.‐P.; Hayne, P. O.; Gallinger, C. L.; Greenhagen, B. T.; McDougall, D. S.; Paige, D. A.
Abstract: The Diviner Lunar Radiometer Experiment on the Lunar Reconnaissance Orbiter (LRO) has been mapping the surface temperatures of the Moon since 5 July 2009. Diviner has since collected over 500 billion radiometric measurements with excellent spatial and local time coverage. However, the most recently published high‐resolution Diviner global maps only use data collected from 2009 to 2016. In this work, we compile ∼13 years of Diviner data to produce improved global maps of nighttime brightness temperature, bolometric temperature, regolith temperature, and rock abundance (RA). Errors in Diviner's pointing have been corrected and past effective field of view modeling has been optimized to improve data georeferencing without spatial interpolation. We estimate an effective resolution of ∼330 m longitudinally and ∼700 m latitudinally at the equator, which corresponds to an improvement of ∼3.5× longitudinally and ∼1.3× latitudinally. In addition, we develop a thermal model that accounts for indirect scattering and emission from surrounding topography. The resulting temperature anomaly maps better highlight variations in temperature caused by thermophysical properties by removing most topographic effects. These improvements allow for the identification of smaller and fainter thermal features than was previously possible. The improved effective resolution of Diviner maps allows for excellent spatial correlation with other high‐resolution data sets. To demonstrate this, we compare Diviner RA to a manual survey of boulders in the Apollo 17 landing site region. We show that Diviner RA correlates well with the areal fraction of rocks larger than ∼1–2 m in diameter visible in LRO Camera imagery. Plain Language Summary: The Diviner Lunar Radiometer Experiment on board the Lunar Reconnaissance Orbiter has been mapping the temperature of the lunar surface since 5 July 2009. Past Diviner data has been used to produce global maps of nighttime temperature and to determine the thermal properties of the surface. However, the most recently published global maps only used data collected from 2009 to 2016. We recreate these global maps using all data available through July 2022: over 5 years of additional data. We implement several improvements, including a correction for errors in instrument pointing, which result in an increase in effective resolution of ∼3.5× and ∼1.3× in the longitudinal and latitudinal directions, respectively. This allows lateral brightness temperature variations to be resolved at a finer scale than was previously possible. In addition, we develop a model that mostly removes the effect of topography on nighttime temperatures. The resulting maps better highlight differences in temperature that are caused by variations in the thermal properties of the surface. Key Points: ∼Thirteen years of Diviner data have been compiled to update the previously published Diviner nighttime temperature and rock abundance maps Improved georeferencing results in sharper maps with an increase in effective resolution of ∼3.5× longitudinally and ∼1.3× latitudinally Thermal modeling which includes terrain scattering and emission removes most of the effects of topography on nighttime temperatures